Sunitinib and Reversible Posterior Leukoencephalopathy Syndrome: the usual suspect but not always the culprit. A case report. - Katopodis Ourania; Lerikou Maria; Karagiorgis Georgios; Arvanitakis Spyridon (Forum of Clinical Oncology)
Sunitinib is a vascular endothelium growth factor inhibitor. This agent may in some cases be associated with life-threatening complications. We report a case of a 64-year-old woman, with a topical recurrence of a papillary renal cell carcinoma (PRCC) who had been treated with sunitinib and presented with generalized convulsive status epilepticus. A diagnosis of Reversible Posterior Leukoencephalopathy Syndrome (RPLS) was made, which was attributed to an abrupt cessation of antihypertensive medication, although there have been cases attributed to sunitinib. Interestingly, after her hypertension was controlled and her clinical symptoms and radiological findings resolved, sunitinib treatment was safely reintroduced, with a good clinical outcome. Aggressive treatment of hypertension allowed the reintroduction of sunitinib, in a case where there were no other significant treatment alternatives. Intensive follow-up and proactive management enabled a successful outcome.